Does timing matter? Investigating preconception stress exposure in relation to infants' memory and emotional development - Low, Grace Jing Hwee (Nanyang Technological University, 2023)
Past research revealed the importance of preconception care in influencing infants’ birth outcomes. Specifically, works on maternal preconception stress arising from extreme experiences (bereavement, trauma) propose that stress occurring within six months of pregnancy may uniquely impact infant development, more so than the prenatal period. However, little knowledge is available on whether this unique period remains crucial when considering less extreme experiences, such as poor mental health, and perceived stress levels from daily activities. Here, we examine whether COVID-related stressors, in addition to the timing at which mothers were exposed to the peak of COVID-related stress, predict infants’ memory and emotional development in a sample of 66 mother-infant dyads. Infants were assessed on their memory for relations between an “item” and its spatial location, and between happy and angry stimuli, while mothers provided retrospective data on stress levels experienced at different timepoints of the COVID pandemic. Results indicate significant main effects of poor maternal mental health and preconception period, and marginally significant main effects of daily stressors on infants’ differential attention towards familiar and novel associations. Overall interaction between poor mental health and preconception period was significant, with post-hoc analyses (p < .10) suggesting that the relationship was only significant when exposure to stress was experienced relatively closer to conception. Findings are discussed in consideration of possible alterations in infant brain development due to maternal stress, and infants’ birth into an unprecedented pandemic. It also highlights the preconception period as a possible intervening timepoint for improved developmental outcomes.